Minecraft for dummies - Cordeiro, Jacob (John Wiley & Sons, 2013)
More than just a game, Minecraft consists of players using an avatar to create or destroy various types of blocks, form fantastic structures, create artwork, and do much more, all in a three-dimensional environment and across various multiplayer servers in multiple game modes. With this fun and friendly beginners guide, you will quickly grasp how to play Minecraft in the three modes of game play: survival, creative, and hardcore. The easy-to-understand writing style walks you through every step of the way, from downloading the game to choosing a gaming platform to defending your creations against monsters and winning the game by defeating the Ender Dragon